The Relationship between Metabolic Effects and the Hormone Cortisol on Anxiety Disorder Patients Treating at Madani Hospital Medan - Nuralita, Nanda Sari (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2024)
Introduction: Anxiety disorder is a condition that is often found in society in general. Long-term anxiety disorders can cause an increase in the hormone adrenaline resulting in an increase in free fatty acids and blood glucose levels, and also cause the release of the hormone cortisol, which is a glucocorticoid hormone synthesized from cholesterol in the adrenal cortex, which can have a negative impact on cardiovascular, metabolic and respiratory effects. Cortisol is commonly known as the "stress hormone", which is only released during stressful conditions. Research method: This research is a numerical analytic study with a cross sectional method, the sampling method is non-probability sampling with consecutive sampling type, with a total sample of 25 people. Results: There was a significant difference between anxiety disorders and an increase in blood sugar(p=0.001, r =0,625) and cholesterol levels (p0.001, r=0,717). There was no significant difference between anxiety disorders and an increase in cortisone hormone with P= 0.366, r=0,189 .Conclusion: There was a significant difference between anxiety disorders and an increase in blood sugar and cholesterol levels, there was no significant difference between anxiety disorders and an increase in the hormone cortisol.